(untitled) (Nigerian Journal of Cooperative Economics and Management, 2026)
Cooperatives recognized as member-owned organization that focus on members’ welfare and socio-economic development face several challenges meeting required expected goals and business objectives. This study examined the influence of entrepreneurial orientation and managerial competence on cooperative performance in Ogun State Nigeria with major focus on cooperatives that engage in business activities. The study is anchored on Resource Based View Theory and Entrepreneurial Orientation Theory, these theories provide sound theoretical basis explaining cooperative performance. Descriptive survey research design was adopted for the study, and data were collected using structured questionnaire. Multi-stage sampling technique was used to select the cooperative societies while simple random sampling was employed to select the respondents of total population of 240, all distributed questionnaires were retrieved and found valid for the research analysis. Descriptive analysis was done using Statistical Package for Social Sciences version 23 while inferential statistical analysis was carried out using Partial Least Squares Structural Equation Modelling (PLS-SEM). Results showed that entrepreneurial orientation significantly influences managerial competence (t=19.703, p=0.000˂0.05) and cooperative performance (t=7.677, p=0.000˂0.05). Results also revealed that managerial competence significantly mediates the relationship between entrepreneurial orientation and cooperative performance (t=11.512, p=0.000˂0.05). The R² values indicated that managerial competence explained 48.1% of the variance, while cooperative performance accounted for 53.0% of the variance explained by the predictor variables. The hypothesis testing results confirmed significant positive relationships among the variables with p-values less than 0.05. The study concludes that entrepreneurial orientation and managerial competence are critical determinants of cooperative performance. It therefore recommends that cooperative societies should strengthen entrepreneurial practices and improve managerial skills to enhance overall organizational performance.